2016
DOI: 10.1097/ccm.0000000000001425
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor Receptor-β Regulates Vascular Smooth Muscle Cell Phenotypic Transformation and Neuroinflammation After Intracerebral Hemorrhage in Mice

Abstract: Objective Platelet-derived growth factor-BB (PDGF-BB) activates platelet-derived growth factor receptor-β (PDGFR-β) and promotes vascular smooth muscle cell phenotypic transformation. Elevated levels of non-muscle myosin IIB (SMemb) are found in secretory smooth muscle cells along with inflammatory mediators, such as intercellular adhesion molecule-1 (ICAM-1), which can amplify neutrophil infiltration into the brain. In the present study, we investigated the role of PDGF-BB/PDGFR-β following intracerebral hemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…These results prompted us to further explore the regulation of IQGAP1 in response in injury and to determine whether IQGAP1 was involved in SMC differentiation. Consistent with the findings of previous studies 21, 42, increased expression of IQGAP1 was observed in LPS-treated SMCs in both the single and co-culture systems. Expression of IQGAP1 was higher in single culture compared with co-culture SMCs.…”
Section: Discussionsupporting
confidence: 92%
“…These results prompted us to further explore the regulation of IQGAP1 in response in injury and to determine whether IQGAP1 was involved in SMC differentiation. Consistent with the findings of previous studies 21, 42, increased expression of IQGAP1 was observed in LPS-treated SMCs in both the single and co-culture systems. Expression of IQGAP1 was higher in single culture compared with co-culture SMCs.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of PDGFR-β by Gleevec and PDGFR-β siRNA effectively preserved the VSMC contractile phenotype and alleviated neuroinflammation in the basal ganglia following ICH. 21 Another study from our laboratory shows that ICH significantly increased passive diameters of cerebral blood vessels compared to sham animals and that PDGFR-β inhibitor imatinib eliminated these differences. In addition, ICH significantly depressed incremental compliance and treatment with imatinib eliminated this effect.…”
Section: Discussionmentioning
confidence: 96%
“…Western blot was performed as previously described [ 35 ]. Mice were transcardially perfused with ice-cold PBS under deep anesthesia, and the brains were removed and separated into two hemispheres at 24 h after ICH or sham surgeries.…”
Section: Methodsmentioning
confidence: 99%